Environmental science : a global concern. - Cunningham, William P.; Cunningham, Mary Ann ;Saigo, Barbara Woodworth (Boston, Massachusetts : McGraw Hill Education, 2003)
Our goal in this book is to provide an up-to-date, introductory view of essential themes in environmental science along with emphasis on details and case studies that will help students process and retain the general principles.
Part one : Environmental science and ecological principles -- Part two : Population, economics, policy, and health -- Part three : Food, land, and biological resources -- Part four : Physical resources -- Part five : Society and environment
Includes index.
Keywords: ENVIRONMENTAL SCIENCES